An everlasting love: The relationship of happiness and meaning - Besika, Anastasia (Frontiers in Psychology, 2023)
Happiness is of great importance to people. Although happiness constitutes a central theme in psychology, the absence of a unifying theory and inconsistent terminology undermine scientific progress. The present article goes beyond attempting to define “types of happiness” or its contributing factors and addresses the role of happiness (i.e., embodied positive emotional patterns) as a function of a dynamic multisystem (i.e., an individual) and its relationship to meaning (i.e., ongoing bidirectional cognitive processes). As a dynamic multisystem, a person strives for stability as they move in physical space, and during their development, across time (i.e., dynamic balance). A primary requirement for dynamic balance is maintaining consistency by connecting the cognitive system to behavior. In psychological terms, such a connection is facilitated by meaning. The model suggests that happiness serves as a marker of a person’s consistency and meaningful interpretations of their lived experience. The model points to a new research direction.